Suicidal Behavior and the Labor Market Productivity of Young Adults - Erdal Tekin; Sara Markowitz (Institute for the Study of Labor (IZA), 2005)
This paper provides a comprehensive analysis of the link between suicidal behaviors and labor market productivity of young adults in the United States. Using data from the National Survey of Adolescent Health (Add Health), we estimate the effects of suicide thoughts and suicide attempts on the work and schooling activities of young adults as well as on their hourly wage rates. The richness of the data set allows us to implement several strategies to control for unobserved heterogeneity and the potential reverse causality. These include using a large set of control variables that are likely to be correlated with both the suicidal behavior and the outcome measures, an instrumental variables method, and a twin fixed effects analysis from the subsample of twin pairs contained in the data. The longitudinal nature of the data set also allows us to control for past suicide thoughts and attempts of the individuals from their high school years as well as the suicide behaviors of the members of their family. Results from the different identification strategies consistently indicate that both suicide thoughts and suicide attempts decrease the hourly wage rate and the probability that a young adult individual works and/or attends school. The results are found to be robust to various specification tests.
Keywords: I1; J24; 330; suicide; wage; employment; Selbstmord; Arbeitskräfte; Jugendliche Arbeitskräfte; USA